Development of Omega-3 and Antioxidant-Rich Bread Spread from Smoked Mackerel and Bambara Groundnut for Cardiovascular Health - Adistira, Ross Mellyana; Marliyati, Sri Anna; Setiawan, Budi (Media Publikasi Cendekia Indonesia, 2025)
Bread spreads can be defined as products that can be spread on bread or as a filling, usually used to add flavor or texture to bread. The taste of bread spread is not only sweet but can be spicy and savory. The purpose of this research was to develop a bread spread made from smoked mackerel with the addition of bambara groundnut and analyze the effect of different formulas on nutrient content, antioxidant activity, and omega-3. This study used a completely randomized design. The analysis test used was One-Way ANOVA with Duncan multiple range test further test with SPSS version 26 and Microsoft Excel 2016 software. The results of this study showed that the highest content of moisture, protein, fat in F1, ash content in F2, while carbohydrates, energy, IC50, and omega-3 in F3. The results of the analysis on bread-spread products contained moisture 31.57-41.06%, ash 4.56-5.00%, protein 15.84-26.82%, fat 28.30-36.24%, carbohydrate 32.14-51.31%, IC50 is 2.66-4.32-ppm, and omega-3 of 1.68-2.6 g/100g. The conclusion of the research showed that the treatment of the ratio of mackerel and bambara groundnut affected on the moisture, protein, and carbohydrate (p<0.05), but did not affect on the ash, fat, omega-3, and antioxidant activity (p>0.05).